The Use of Signing Space in a Shared Sign Language of Australia - Bauer, Anastasia (Sign Language Typology [SLT], 2014)
In this book, an Australian Aboriginal sign language used by Indigenous people in the North East Arnhem Land (Northern Territory) is described on the level of spatial grammar. Topics discussed range from properties of individual signs to structure of interrogative and negative sentences. The main interest is the manifestation of signing space - the articulatory space surrounding the signers - for grammatical purposes in Yolngu Sign Language.